Status Kesuburan Perairan Laut ditinjau dari Keragaman Plankton di Kawasan Kepala Burung, Papua Barat - Suharno Suharno; Daniel Lantang (Jurnal Biologi Papua, 2012)
Papua is well known asa megabiodiversity area because it has high diverse biological resources; on the other hand the diversity of plankton biota has not been much studied. Plankton has an important role in the food chain system in the waters, both at sea, freshwater and brackish. The purpose of this study was to determine the level of marine water fertility based on the presence of plankton diversity in the Kepala Burung, West Papua Province. The method used was a survey, with sampling at six (6) point coordinates in Manokwari and Sorong regency. The results showed that there were 66 types of plankton found in marine waters Manokwari and Sorong, Kepala Burung region, West Papua Province. Therefore these waters are still quite fertile with diversity index (H') in Manokwari was 2.80 (32 types of plankton), whereas in Sorong 3.16 (48 species).Key words: plankton, water fertility, Manokwari, Sorong, West Papua Province.